Compliance Culture in Urban Co-Operative Banks: Challenges ‎and Strategies - Nair. B, Gopakumaran; Alamelu , K.; Karthick , AV. (International Journal of Accounting and Economics Studies, 2025)
Urban Co-operative Banks (UCBs) serve as vital financial intermediaries for urban and semi-urban populations, particularly lower and middle-income segments. However, these institutions face significant challenges in maintaining robust compliance frameworks within an in‎creasingly complex regulatory environment. This study examines compliance culture across five critical dimensions through empirical analysis of 232 UCB employees in Maharashtra. The research employs agency theory and institutional theory frameworks to understand compliance behavior patterns. Key findings reveal strong leadership commitment (88% positive responses) and employee awareness, but critical ‎gaps in accountability enforcement (41% reporting inconsistent accountability), fear-based reporting barriers (36% experiencing retaliation ‎concerns), and insufficient recognition systems (45% lacking adequate compliance rewards). The study contributes to compliance literature ‎by providing empirical evidence of the disconnect between compliance awareness and implementation effectiveness in cooperative banking ‎institutions. Strategic recommendations include implementing transparent accountability mechanisms, establishing confidential reporting ‎systems, developing structured incentive programs, and creating continuous policy update frameworks.